Kearifan Lokal Suku Osing: Kajian Budaya Sebagai Media Pembelajaran Sosiologi - Midya Aulia Nisak; Siti Komariah; Wilodati Wilodati (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
The Osing tribe in Kemiren Village still respects and preserves ancestral traditions such as: Mepe mattress, Barong Ider Bumi, Kebo-keboan, Ithuk-ithukan, Angklung Paglak, Kawin Colong, Mocoan Lontar, Barong Caruk, Gandrung dance etc. From the various kinds of local wisdom that exist in the Banyuwangi community, this can enrich knowledge and of course it can be used as teaching material in the learning process, this is a form of preserving regional culture. The existence of the traditions of the Osing tribal community in the world of education is armed with various forms of local wisdom that exist in the Osing tribe. This is a form of cultural heritage that can be used as a source of learning at the elementary to senior high school levels in Banyuwangi Regency. Local wisdom values ​​can be implemented in all subjects, especially in sociology. Implementation of an educational approach based on local wisdom in sociology learning in schools is one of the solutions related to problems that exist in the community environment. Students are invited to be sensitive to their social environment and with an approach based on local wisdom students are invited to find out what local wisdom exists in their respective areas. Through sociology subjects at school, students are directed to be able to become virtuous Indonesian citizens by upholding local wisdom values, loving cultural differences, and being able to coexist regularly within the community.